2016
DOI: 10.1017/iop.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Other Important Questions: When, How, and Why Do Cultural Values Influence Performance Management?

Abstract: Adler et al. (2016) raise some controversial issues about whether performance rating systems should be eliminated or not. We strongly believe that the decision to do away with performance ratings is premature because more research needs to be done, as suggested by “the better questions” that Adler et al. listed at the end of the focal article. We propose that those questions can be extended further by testing them in other cultures and supplemented with these questions: When, how, and why do cultural values in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
1
17
0
2
Order By: Relevance
“…Several researchers have identified discrepancies between self‐rated and other‐rated outcomes (e.g., engagement) because individuals tend to evaluate their own outcomes leniently (Adler et al, ; Harris & Schaubroeck, ; Heidemeier & Moser, ). The research on performance management has focused mainly on leniency of self‐rating performance appraisals, and these studies have been primarily conducted in Western cultures (Cho & Payne, ). In contrast, Farh, Dobbins, and Cheng () showed that self‐raters in China rated their own performance lower than did their supervisors, colleagues, and subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have identified discrepancies between self‐rated and other‐rated outcomes (e.g., engagement) because individuals tend to evaluate their own outcomes leniently (Adler et al, ; Harris & Schaubroeck, ; Heidemeier & Moser, ). The research on performance management has focused mainly on leniency of self‐rating performance appraisals, and these studies have been primarily conducted in Western cultures (Cho & Payne, ). In contrast, Farh, Dobbins, and Cheng () showed that self‐raters in China rated their own performance lower than did their supervisors, colleagues, and subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that dialogue and feedback, as carried out in the PM process in low power distance societies (Chiang & Birtch, 2010), were not encouraged in appraisals in high power societies (Chow, 1995; Singh et al, 2013). Fear of conflict and confrontation reduced the usability of direct feedback, and detailed discussions or developmental discussions were unlikely to take place (Cho & Payne, 2016). Further, when evaluated and given a final rating, employees working in high power distance societies were more likely to accept the evaluation decisions of those in the top position; thus, the resulting appraisals were more evaluative, linked with bonuses, incentives, and promotions (Chiang & Birtch, 2010; Festing & Knappert, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that appraisees may receive more favourable ratings because of good relations with subordinates in collectivist societies, as noted in the study of a private bank in Bangladesh (Hossain et al, 2015), in organizations in China (Gu & Nolan, 2017; Wang et al, 2019), in a performance appraisals study in Saudi Arabia (Harbi et al, 2017), and in Tunisia (Yahiaoui, 2015). Also, negative ratings or penalties, which are a part of PMS design, may not be used to avoid negative social consequences (Cho & Payne, 2016), and to save face (Hossain et al, 2015; Yahiaoui, 2015), including even to the extent of manipulating subordinates' annual confidential reports (Hossain et al, 2015). Similarly, confrontational, evaluative, and calculated appraisals were avoided in many societies to promote harmony (Harbi et al, 2017; Lunnan et al, 2005; Yahiaoui, 2015; Yang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason Adler et al (2016) identify for abolishing performance ratings is low levels of interrater agreement between raters on the same performance dimensions. Within a similar vein, Cho and Payne (2016) argue that cultural values may be related to the discrepancy observed in performance ratings. The purpose of the present study is to further explore the role of cultural values on evaluation of job performance behaviors and resulting performance ratings.…”
mentioning
confidence: 96%